Why Thailand should consider promoting Neonatal circumcision? - Srithanaviboonchai K. (2014)
Male circumcision (MC) has been proven to reduce the risk of HIV transmission. The WHO and UNAIDS jointly recommend the international community consider MC as an HIV prevention measure. MC reduces the risk of acquiring other sexually transmitted infections (STIs) among men, urinary tract infections among children and penile cancer. Lowering the prevalence of STIs in men may reduce the incidence of STIs among women. High levels of adult MC are difficult to achieve in cultures where it has not been customary. Adult MC is associated with a high prevalence of post-operative complications. Neonatal male circumcision (NC) is simpler, safer, and cheaper. Higher coverage with MC can be achieved through NC. Thailand is a good country to promoting NC for the following reasons: most HIV infections are contracted through heterosexual transmission, there is a low MC rate, most newborn deliveries occur in hospitals, there is a relatively strong health care infrastructure and Thailand has well developed HIV care services. Issues of concern regarding promoting NC include length of time before seeing benefits, cost effectiveness of the intervention, the burden to the health care delivery system and concerns about children's rights. NC is an efficacious HIV prevention strategy that should be considered by those involved in HIV/AIDS prevention planning in Thailand. Further studies are needed to determine whether NC should be promoted in Thailand.